Continuous‐light versus pulsed‐light accelerated corneal crosslinking with ultraviolet‐A and riboflavin. Issue 3 (March 2018) - Zhu, Yirui; Reinach, Peter S.; Zhu, Hanlei; Li, Ling; Yang, Fan; Qu, Jia; Chen, Wei
Abstract : Purpose: : To determine whether the pulsed‐light ultraviolet‐A (UVA) accelerated corneal crosslinking (CXL) procedure is more efficacious and selective than its continuous‐light counterpart in rabbits. Setting: : School of Ophthalmology and Optometry, Wenzhou Medical University, Wenzhou, Zhejiang, China. Design: : Experimental study. Methods: : Fifty‐four rabbits were divided into 2 groups. Group 1 had continuous‐light accelerated CXL using 9 mW/cm 2 UVA for 10 minutes (5.4 J/cm 2 ). Group 2 had pulsed‐light accelerated CXL by exposing them to 9 mW/cm 2 UVA for 20 minutes (1 second on/1 second off). Corneal stromal demarcation line depth, in vivo confocal microscopic analysis, biomechanical stiffness, endothelial cell density, and keratocyte apoptosis were measured after performing these CXL procedures. Results: : The mean stromal demarcation line depth was 254.7 μm ± 47.4 (SD) in Group 1 and 341.1 ± 36.1 μm in Group 2 ( P < .01). One day after CXL, confocal analysis and histological staining identified keratocyte apoptotic fragments in the anterior stroma in the Group 2 corneas whereas all cells were obliterated in Group1. Seven days after treatment, the thicknesses in Group 1 were significantly greater than those in Group 2 ( P < .05). Endothelial cell losses were reversible; however, in Group 1, some losses were still evident on day 7. Increases in both the stress–strain relationship and tangent modulus in Group 2 were greater than those in Group 1. Conclusion: : The pulsed‐light accelerated CXL protocol was less injurious and more efficacious at inducing CXL than the continuous‐light accelerated CXL protocol in rabbit corneas.